Nursing process used in a user with pneumonia due to SARS-Cov-2 diagnosis - Peralta-Peña, Sandra Lidia (Universidad de Sonora, 2020)
Introduction: After the pandemic due to SARS-Cov-2, the participation of the professional nursing has been a core part of the success in the healthcare of users who have been diagnosed with COVID-19, due to a high mortality rate worldwide. The use of internal nursing methodologies makes the difference for a better clinical reasoning, thus assuring a diagnostic and therapeutic accuracy. Objective: Present a proposal of nursing care following methods and resources of the own nursing discipline. Methodology: The nursing process as intervention method and the taxonomies of NANDA, NOC, and NIC were used. The accuracy of the diagnosis was estimated through the Lunney’s Accuracy of Nursing Diagnoses Scale and the prioritization of diagnosis with the reasoning network of the AREA model. Presentation of the case: Female user of 67 years of age diagnosed with pneumonia due to SARS-Cov-2 who entered to the intensive therapy unit after twelve days of hospitalization in internal medicine and seven days of invasive ventilation support with sedoanalgesia. Conclusions: The applications of the nursing process and complementary resources allowed obtaining more precise diagnoses, their prioritization, and the development of the development of the therapeutic judgment during intervention.